Inflation and Inequality - Stefania Albanesi (Luxembourg Income Study (LIS), 2001)
Cross-country evidence on inflation and income inequality suggests that they are positively correlated. The hypothesis that this correlation is the outcome of a distributional conflict underlying the determination of fiscal policy is explored.
Keywords: 330; Inflation; Einkommensverteilung; Finanzpolitik; Theorie; Korrelation